Percepción emocional ante el Covid-19 y el aislamiento social obligatorio - Lenti Canepa, Martha (2022)
The pandemic caused by COVID-19 has been an unexpected experience for the world at large. In March 2020, the World Health Organization (WHO) declared COVID-19 (SARS-CoV-2) disease a pandemic. Worldwide, strategies to control the COVID-19 pandemic have included social distance and isolation, measures also adopted in Peru. The general aim of the present study is to determine the characteristics of emotional perception in adults towards COVID-19 and mandatory social isolation. This is a comparative-descriptive research study. The sample consisted of 1207 adults. The instrument used was a 31-item closed-ended descriptive survey, including multiple options, reviewed by peers, and designed by the researchers. It was disseminated through the CAWI system. The most important results regarding the emotional perception of the experiences with COVID-19 are as follows: 54% admitted experiencing mostly fear, 27% felt turmoil, and 18% experienced sadness. The following were found in relation to mandatory social isolation (ASO, by its acronym in Spanish): fear was experienced by 37%, sadness by 21% and anger by 4% of respondents. The psychosocial reasons for the perceived differences toward the threat of the virus belonged to the following aspects: healthcare, possibility of contagion and death. Finally, respondents predominantly visualized changes in their future lives, having to come to terms with coexisting with the virus.